Pengaruh Kualitas Pelayanan, Good Coorporate Governance Dan Strategi Pemasaran Terhadap Loyalitas Nasabah - Restu Fajar Maulida; Nadia Roosmalita Sari (LPPM ISNJ Bengkalis, 2022)
This study aims to show the effect of service quality, good corporate governance, and marketing strategy on customer loyalty at Bank Panin Dubai Syariah Malang regional office. The research data used is primary data in a questionnaire with quantitative methods. The sampling method used non-probability sampling with Roscoe theory and obtained 40 respondents. Data were analyzed by the multiple linear regression method using SPSS software. Prior to data analysis, validity, reliability, and classical assumptions were tested. The results showed that service quality, good corporate governance, and marketing strategy simultaneously affected customer loyalty. At the same time, partial service quality, good corporate governance, and marketing strategy have a positive and significant effect on customer loyalty. This research can complement existing theories and help Panin Dubai Syariah Bank Malang regional office improve service quality, governance, and marketing strategies to increase customer loyalty.